The Effectiveness of Group Counseling Intervention for Vocational High School Students with Addictive Behavior to Playing Online Games - Perdini, Tiara Anggita; Indrawati, Erdina (International Journal of Psychology and Health Science, 2024)
This study aims to determine the extent to which group counseling is effective in handling cases of online game addiction among students at vocational schools. Before being decided whether addicted to playing games, the subjects will go through observations on their surroundings, interviews and psychological tests. The WBIS test and Graphic test are the psycho-test tools in use. The research subjects consisted of three (3) tenth-grade students from a vocational school majoring in Network Engineering. After the examination, the next step is giving the intervention. This study involves an intervention in the form of group counseling techniques regarding the self-management strategy to help overcome the issues. From previous results, changes to the subject are visible. They are getting used to sharpening and effectively managing their skills besides other activities. Hopefully, future research will be able to employ group counseling techniques to other groups using the longitudinal method, which hopefully can explore changes in behavior over a longer period.